The Activity of the Judge Peliksas Bugailiškis: Between law and ethnography. Findings of the Šiauliai District Court Criminal Cases of the Lithuania Interwar Period - Kazdanas, Robertas (PRAWO i WIĘŹ, 2025)
The aim of this paper is to present the reflections on the professional activity of Peliksas Bugailiškis (1883-1965), a unique figure in Lithuanian history. In particular, the author attempts to briefly present Bugailiškis’s path to the position of judge and his liberal ideas on the introduction of suspended sentences into Lithuanian criminal law, based on the 1903 adaptation of the Criminal Code of the Russian Empire. During the inter-war period, while working as a judge, Bugailiškis was also an active member of society and local culture, sharing his passion for Lithuanian ethnology and museology. The surviving documentation about Bugailiškis provided an interesting moral approach to trace his views on criminal offences and their links with traditional transgressions. The author argues that despite the ethnological nature of the research campaigns initiated by Bugailiškis, they are also relevant to the field of criminology and social policy in inter-war Lithuania. In this context, the paper is useful in revealing the broader issues of society’s negative attitudes towards abortion or the birth of an illegitimate child, which should have been addressed by the Lithuanian legal system.